Exercise increases the release of NAMPT in extracellular vesicles and alters NAD+ activity in recipient cells. Issue 7 (3rd June 2022) - Chong, Mee Chee; Silva, Anabel; James, Patrick F.; Wu, Sam Shi Xuan; Howitt, Jason
Abstract: Aging is associated with a loss of metabolic homeostasis, with cofactors such as nicotinamide adenine dinucleotide (NAD + ) declining over time. The decrease in NAD + production has been linked to the age‐related loss of circulating extracellular nicotinamide phosphoribosyltransferase (eNAMPT), the rate‐limiting enzyme in the NAD + biosynthetic pathway. eNAMPT is found almost exclusively in extracellular vesicles (EVs), providing a mechanism for the distribution of the enzyme in different tissues. Currently, the physiological cause for the release of eNAMPT is unknown, and how it may be affected by age and physical exercise. Here, we show that release of small EVs into the bloodstream is stimulated following moderate intensity exercise in humans. Exercise also increased the eNAMPT content in EVs, most prominently in young individuals with higher aerobic fitness. Both mature fit and young unfit individuals exhibited a limited increase in EV‐eNAMPT release following exercise, indicating that this mechanism is related to both the age and physical fitness of a person. Notably, unfit mature individuals were unable to increase the release of eNAMPT in EVs after exercise, suggesting that lower fitness levels and aging attenuate this important signalling mechanism in the body. EVs isolated from exercising humans containing eNAMPT were able to alter the abundance of NAD + and SIRT1 activity in recipient cells compared to pre‐exercise EVs, indicating a pathway for inter‐tissue signalling promoted through exercise. Our results suggest a mechanism to limit age‐related NAD + decline, through the systemic delivery of eNAMPT via EVs released during exercise. Abstract : Aging is associated with decreased NAD + production, which is critical for maintaining tissue and metabolic homeostasis. Here, we identified that moderate intensity exercise in humans can result in the release of NAMPT in extracellular vesicles, that when delivered to recipient cells promotes NAD + biosynthesis and SIRT1 activity. Our findings show an exercise‐based mechanism for the production of NAD + that differs between age groups, moderated by the release of eNAMPT in EVs.